1985
DOI: 10.1128/aem.49.4.914-919.1985
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiology of avian influenza: effect of season on incidence in sentinel ducks and domestic turkeys in Minnesota

Abstract: Sentinel ducks and domestic turkey flocks were monitored for influenza infection during a 4-year period. The onset of infection among ducks was similar each year, occurring in late July or early August. Influenza in turkeys was also shown to be seasonal, but the usual onset was 6 to 8 weeks after the detection of influenza in sentinel ducks. Possible explanations for the delayed infection in turkeys are (i) increased waterfowl activity associated with fledging and congregating in late summer and early fall; (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…The higher risk observed in waterfowl might be related to the species relatedness with migratory wild waterfowl, their long lifespan and the fact that these PTs are mainly kept outdoors which is associated with a higher risk of exposure to AIVs from the environment and wild fauna. 19,33,34 Commercial layers were the most targeted PT. This PT was targeted assuming a higher risk due to their lifespan and their production characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk observed in waterfowl might be related to the species relatedness with migratory wild waterfowl, their long lifespan and the fact that these PTs are mainly kept outdoors which is associated with a higher risk of exposure to AIVs from the environment and wild fauna. 19,33,34 Commercial layers were the most targeted PT. This PT was targeted assuming a higher risk due to their lifespan and their production characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Winter in both humans and poultry (in Asia) [9,10] Bacterial Pneumonia Acute c, d, and e Peaks in midwinter (in the US); it is associated with influenza [11] Brucellosis Acute b Spring and summer in wildlife and livestock; the timing relates to the birthing season; peaks in the summer in humans [12] Buruli ulcer Chronic c Varies by location; some studies have not observed seasonality [13] Chagas disease Acute and chronic a Peaks in spring and summer in countries with distinct seasons [14] Chickenpox acute f Peak in spring in the Northern and Southern Hemisphere [15] Chikungunya Acute a Rainy season when vector density peaks. [16] Cholera Acute c, d, and g Seasonality is stronger in countries further from the equator; outbreaks generally occur in warm months [17] Crimean-Congo hemorrhagic fever Acute a Seropositivity in livestock correlates with seasonal changes in tick parasitism; human cases correlate with livestock seropositivity [18] Cryptosporidium Acute c Increased risk of cryptosporidium associated with high ambient temperature and high rainfall [19] Cutaneous leishmaniasis Acute and chronic a and b Strong seasonal variation with elevated incidence from October to March (in Tunisia).…”
Section: Descriptionmentioning
confidence: 99%
“…Waterfowl, exhibition game fowl and poultry flocks reared on backyard premises have been used as sentinels for active surveillance for avian diseases of interest to the commercial poultry industry and regulatory agencies (McBride et al 1991;Johnson et al 2004). Sentinel ducks have been used effectively to determine the presence of AIV and timing of infection associated with the arrival of wild migratory waterfowl in wetland habitats (Turek et al 1984;Sinnecker et al 1982a,b;Halvorson et al 1983;Halvorson et al 1985;Kelleher et al 1985).…”
Section: Sentinel Speciesmentioning
confidence: 99%
“…Major advantages of sentinel bird surveillance include the previous success of such systems to effectively detect AIV (Halvorson et al 1983;Halvorson et al 1985) and the applicability in areas in which other methods cannot be used (e.g. urban areas).…”
Section: Sentinel Speciesmentioning
confidence: 99%